ҚАЗАҚСТАН РЕСПУБЛИКАСЫНДА АУЫЛШАРУАШЫЛЫҚ КООПЕРАЦИЯСЫН МЕМЛЕКЕТТІК ҚОЛДАУ ШАРАЛАРЫН ДАМЫТУ МӘСЕЛЕЛЕРІ (Journal of actual problems of jurisprudence, 2019)
In this article the author examines the legal positions with the state support measures in agricultural co-operatives and makessuggestions to improve it.